Corporate bond market in Poland: Prospects for development - Jakub Kubiczek (Journal of Risk and Financial Management, 2020)
The Polish corporate bond market does not have a history as long as the American one, however, it is characterized by stable annual growth. The growth of the market is related to the growth of its liquidity and is determined by a number of entities, both on the demand and the supply side. The aim of the study was to present the structure of the Catalyst market and bond trading in Poland. The study also discusses the market's development and identifies the factors that determine this development. Based on reports concerning trading on the Catalyst market, a huge growth was noticed in the 10 years since the market's establishment. Forecasts indicate that the growth will continue. The outbreak of the SARS-CoV-2 pandemic will cause the market development to be slower than the model's forecast, although the data for the first nine months of 2020 suggest that the upward trend will be maintained. Moreover, for the market to continue to thrive, a rating must be compulsory for corporate bond issuers. A comparison of the ratings of individual issuers enables investors to analyze the risk and profitability of corporate bonds in an easier way.
Keywords: 330; corporate bond market; market transparency; bond liquidity; corporate finance; Polish bond market